Unchecked hyperparathyroidismand von recklinghausen’s disease of bone: Great mimicker in diagnosis - Mishra, Pankaj Kumar; Nadeem, Mohammed; Khare, Anshul; Singh, Bipin; Shukla, Jiten; Chaudhary, Devendra (Indian Journal of Case Reports, 2019)
Incidence of new cases of a severe form of unchecked primary hyperparathyroidism is decreasing day by day. Here, we report the case of a 40-year-old female patient of primary hyperparathyroidism with a maiden visit to the hospital with multiple osteolytic lesions and multiple pathological fractures. The diagnosis was installed and managed accordingly.